2011
DOI: 10.1080/14616734.2011.602245
|View full text |Cite
|
Sign up to set email alerts
|

Attachment mental states and inferred pathways of development in borderline personality disorder: a study using the Adult Attachment Interview

Abstract: We report the outcome of an investigation on how specific attachment states of mind and corresponding risk factors related to different DSM Axis I comorbidities in subjects with BPD. Mental representations of attachment in four BPD sub-groups (BPD and Anxiety/Mood Disorders, BPD and Substance Use and Abuse Disorders, BPD and Alcohol Use and Abuse Disorders, and BPD and Eating Disorders) were assessed in 140 BPD subjects using the Adult Attachment Interview (AAI). In addition to the global attachment picture in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 25 publications
3
24
0
12
Order By: Relevance
“…The possibility of insecure or disorganized attachment is higher when the primary relationship is inadequate and children are exposed to extreme life events such as institutional care (Vorria et al 2003;Zeanah et al 2005). If an insecure pattern is combined with disorganization of attachment, the risk for specific impairment in psychological well-being definitely increases (van IJzendoorn et al 1999;Lyons-Ruth & Jacobvitz 2008;Barone et al 2011).…”
Section: In Terms Of Attachment What Counts In Adoption?mentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of insecure or disorganized attachment is higher when the primary relationship is inadequate and children are exposed to extreme life events such as institutional care (Vorria et al 2003;Zeanah et al 2005). If an insecure pattern is combined with disorganization of attachment, the risk for specific impairment in psychological well-being definitely increases (van IJzendoorn et al 1999;Lyons-Ruth & Jacobvitz 2008;Barone et al 2011).…”
Section: In Terms Of Attachment What Counts In Adoption?mentioning
confidence: 99%
“…If an insecure pattern is combined with disorganization of attachment, the risk for specific impairment in psychological well‐being definitely increases (van IJzendoorn et al . 1999; Lyons‐Ruth & Jacobvitz 2008; Bakermans‐Kranenburg & van IJzendoorn 2009; Barone et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These classifications have been associated with diverse psychiatric disorders in adults such as PTSD (Harari et al, 2009), borderline personality disorder (Agrawal, Gunderson, Holmes, & Lyons-Ruth, 2004;Barone, Fossati, & Guiducci, 2011;Lyons-Ruth, Brumariu, Bureau, Hennighausen, & Holmes, 2014;Lyons-Ruth, Bureau, Holmes, Easterbrooks, & Brooks, 2013), and anti-social personality disorder (Levinson & Fonagy, 2004;van IJzendoorn 2 M.-J. van Hoof et al et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…In studies reviewed by Agrawal et al using the AAI from 50% to 80% of patients with BPD were classified as "unresolved." On the other hand, a recent study by Barone, Fossati, and Guiducci (2011) using the AAI found Insecure Organized (Dismissing 51% and Preoccupied 35%) and Disorganized (Unresolved-Cannot Classify) categories (40%) were overrepresented on a global view of subjects with BPD, with significantly different distribution of attachment classification found in four BPD subgroups (co-occurring mood/anxipossible when significant structural dissociation (van der Hart, Nijenhuis, & Steele, 2006) is present, because in these cases a specific "progressive approach" is needed to identify and work through dissociative phobias and safely access traumatic material (Gonzalez & Mosquera, 2012). The relationship between structural dissociation and BPD is too complex to be developed in this article (see Mosquera et al, 2011, for a comprehensive review of this topic).…”
Section: Attachment and Bpdmentioning
confidence: 95%